GRP78 expression inhibits insulin and ER stress–induced SREBP-1c activation and reduces hepatic steatosis in mice - Kammoun, Hélène L.; Chabanon, Hervé; Hainault, Isabelle; Luquet, Serge; Magnan, Christophe; Koike, Tatsuro; Ferré, Pascal; Foufelle, Fabienne (The Journal of clinical investigation, 2009)
Hepatic steatosis is present in insulin-resistant obese rodents and is concomitant with active lipogenesis. Hepatic lipogenesis depends on the insulin-induced activation of the transcription factor SREBP-1c. Despite prevailing insulin resistance, SREBP-1c is activated in the livers of genetically and diet-induced obese rodents. Recent studies have reported the presence of an ER stress response in the livers of obese ob/ob mice. To assess whether ER stress promotes SREBP-1c activation and thus contributes to lipogenesis, we overexpressed the chaperone glucose-regulated protein 78 (GRP78) in the livers of ob/ob mice using an adenoviral vector. GRP78 overexpression reduced ER stress markers and inhibited SREBP-1c cleavage and the expression of SREBP-1c and SREBP-2 target genes. Furthermore, hepatic triglyceride and cholesterol contents were reduced, and insulin sensitivity improved, in GRP78-injected mice. These metabolic improvements were likely mediated by restoration of IRS-2 expression and tyrosine phosphorylation. Interestingly, GRP78 overexpression also inhibited insulin-induced SREBP-1c cleavage in cultured primary hepatocytes. These findings demonstrate that GRP78 inhibits both insulin-dependent and ER stress-dependent SREBP-1c proteolytic cleavage and explain the role of ER stress in hepatic steatosis in obese rodents.